Clinical assessment as a part of an early warning score—a Danish cluster-randomised, multicentre study of an individual early warning score. Issue 7 (July 2022) - Nielsen, Pernille B; Langkjær, Caroline S; Schultz, Martin; Kodal, Anne Marie; Pedersen, Niels Egholm; Petersen, John Asger; Lange, Theis; Arvig, Michael Dan; Meyhoff, Christian S; Bestle, Morten H; Hølge-Hazelton, Bibi; Bunkenborg, Gitte; et al.
Summary: Background: The clinical benefit of Early Warning Scores (EWSs) is undocumented. Nursing staff's clinical assessment might improve the prediction of outcome and allow more efficient use of resources. We aimed to investigate whether the combination of clinical assessment and EWS would reduce the number of routine measurements without increasing mortality. Methods: We did a cluster-randomised, crossover, non-inferiority study at eight hospitals in Denmark. Patients aged 18 years or older, admitted for more than 24 h were included. Admissions to paediatric or obstetric wards were excluded. The participating hospitals were randomly assigned 1:1 to start as either intervention or control with subsequent crossover. Primary outcomes were 30-day all-cause mortality (non-inferiority margin=0·5%) and average number of EWS per day per patient. The intervention was implementation of the Individual EWS (I-EWS), in which nursing staff can adjust the calculated score on the basis of their clinical assessment of the patient. I-EWS was compared with the National Early Warning Score (NEWS). The study is registered at ClinicalTrials.gov, NCT03690128 and is complete. Findings: Unique admissions longer than 24 h were included from Oct 15, 2018 to Sept 30, 2019. Of 90 964 patients assessed, n=46 470 were assigned to the I-EWS group and n=44 494 to the NEWS group. Mortality within 30 days was 4·6% for the I-EWS group, and 4·3% for the NEWS group (adjusted odds ratio 1·05 [95% CI 0·99–1·12], p=0·12). In subgroup analyses I-EWS showed increased 30-day mortality for hospitals that did I-EWS in fall–winter, which was probably due to seasonality, and within patients admitted in a surgical specialty. Overall risk difference was 0·22% (95% CI −0·04 to 0·48) meaning that the non-inferiority criteria were met. The average number of scorings per patient per day was reduced from 3·14 to 3·10 (ie, a relative reduction of 0·64% [95% CI −0·16 to −1·11], p=0·0084) in the I-EWS group. Interpretation: Including clinical assessment in I-EWS was feasible and overall non-inferior to the widely implemented NEWS in terms of all-cause mortality at 30 days, and the number of routine measurements was minimally reduced. However I-EWS should be used with caution in surgical patients. Funding: Capital Region Research Foundation, Gangsted Foundation, Candys Foundation, Herlev-Gentofte Hospital Research Foundation, Laerdal Foundation, and The Foundation of Director Boennelycke and wife.